ANALISIS PENGARUH IMPLEMENTASI GOOD CORPORATE GOVERNANCE, KEPEMILIKAN DAN UKURAN BANK TERHADAP KINERJA PERBANKAN (STUDI EMPIRIS PADA BANK YANG TERDAFTAR DI BEI TAHUN 2013 S/D 2015) - Nirmayana Nirmayana; Ria Nelly Sari; Novita Indrawati (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
The purpose of this study is to analyze the influence of Good CorporateGovernance Implementation, Ownership, and Size on Performance of Bank listed on Indonesian Stock Exchange for period 2013 - 2015. Bank performance measured by Return On Assets (ROA) and Net Interest Margin (NIM). The population of this study are banks which listed in Indonesian Stock Exchange2013 – 2015. The sample obtained based on purposive sampling method. Based on the criteria, 35 banks are chosen as samples in this study. The data were analyzed by using multiple regressions assisted with SPSS Version 19. The result of this study showed that good corporate governance implementation have no influence on ROA and NIM. Then, Ownership have influence on ROA but have no influence on NIM. In the other hand, Size of bank have influence on ROA and NIM.The purpose of this study is to analyze the influence of Good CorporateGovernance Implementation, Ownership, and Size on Performance of Bank listed on Indonesian Stock Exchange for period 2013 - 2015. Bank performance measured by Return On Assets (ROA) and Net Interest Margin (NIM). The population of this study are banks which listed in Indonesian Stock Exchange2013 – 2015. The sample obtained based on purposive sampling method. Based on the criteria, 35 banks are chosen as samples in this study. The data were analyzed by using multiple regressions assisted with SPSS Version 19. The result of this study showed that good corporate governance implementation have no influence on ROA and NIM. Then, Ownership have influence on ROA but have no influence on NIM. In the other hand, Size of bank have influence on ROA and NIM.